Analisis Kausalitas Dengan Pendekatan Error Correction Model: Studi Empiris Hutang Luar Negeri Dengan Defisit Anggaran APBN di Indonesia (1990.1 – 2006.4) - Suharno Suharno (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
Indonesia needs enough number of funds. Actually, there are two kinds of the fund sources : the domectic funds and foreign funds. In Indonesia the number of of domestic funds is often smaller than that is needed, so forcing to search for alternative fund sources, that is, foreign loan. Foreign loan haves big risk. The inflow of foreign loan will incrase money incirculation, so that it can trigger inflation. On the other hand, it is obligation to pay in installment of the principal loan and its interest. This is a problem, that annually always burdens the Indonesian budget. The economic situation in Indonesia more difficult for the future. Actually from year to year, the fund need in a country is increasingly bigger. From this background, it is interesting to study how causality correlation pattern between foreign loan and budget deficit. The result of this research showed that there are two-way causality correlations with error correction model (ECM), namedly, foreign loan influences budget deficit and budget deficit influences foreign loan. Key words: foreign loan, budget deficit.